Therapeutic strategies targeting SREBP transcription factors: an update to 2024 - Yongdan Wang; Haitao Xiao; Lina Lai; Zuguo Zheng (Acta Materia Medica)
In addition to regulating lipid biosynthesis and uptake, sterol regulatory element binding protein (SREBP) is involved in mediating biological signaling networks. SREBP is a key transcription factor in the regulation of physiologic and pathologic lipid metabolism processes. “SREBP” was used as a keyword in searches on the Web of Science, Elsevier, Science Direct, and CNKI databases for relevant literature from 2021 to October 2024; the search results were analyzed. SREBP is first synthesized as an inactive precursor, then cleaved to release active NH2-terminal domains. Mature SREBP enters the nucleus and promotes transcription of downstream genes by binding to the promoter elements of target genes. The classical pathway of SREBP precursor activation refers to transporter cleavage that is dependent on SCAP in response to signals from intracellular sterol depletion. However, in the case of endoplasmic reticulum stress, SREBP is activated via caspase-2 and independent of feedback inhibition by steroids or excess lipid uptake. Furthermore, the mechanism of action underlying SREBP in different diseases, as well as synthetic and natural compounds that inhibit SREBP activity, are summarized to provide new insights into SREBP as a therapeutic target for diseases.